New species and records of Anthicidae Latreille, 1819 (Coleoptera) from Taiwan with a key to Asian Nitorus Telnov, 2007 species with gibbose pronotum - Telnov, Dmitry (Zootaxa, 2024)
Descriptions of the following four new species of Anthicidae Latreille, 1819 from Taiwan are presented: Microhoria bunun, M. lingua, M. taguan, Nitorus mediator spp. nov. Nitorus mediomaculatus (Pic, 1913) stat. restit., comb. nov. is rescued from the synonymy with N. trigibber (Marseul, 1876), a new combination is proposed (from Anthicus Paykull, 1798), and a lectotype designation is made. New distribution records of anthicids from Taiwan are provided. Asian species of Nitorus Telnov, 2007 with distinctly gibbose pronotum are keyed and Nitorus sathulaz sp. nov. from northern Vietnam is described.